Asymmetry in Uranus' high energy proton radiation belt - Acevski,M; Masters,A; ZomerdijkRussell,S (Geophysical Research Letters, 2024)
Uranus is one of the least explored planets in our solar system, it exhibits a unique magnetic field structure which was observed by NASA's Voyager 2 mission nearly 50 years ago. Notably, Uranus displays extreme magnetic field asymmetry, a feature exclusive to the icy giants. We use the Boris algorithm to investigate how high energy protons behave within this unusual magnetic field, which is motivated by Voyager 2's observation of lower-than-expected high energy proton radiation belt intensities at Uranus. When considering full drift motions of high energy protons around Uranus, the azimuthal drift velocity can vary by as much as 15% around the planet. This results in areas around Uranus where particles will be more depleted (faster drift) and other regions where there is a surplus of particles (slower drift). This could provide a partial explanation for the “weak” proton radiation belts observed by Voyager 2.